2021
DOI: 10.3389/fpubh.2021.690421
|View full text |Cite
|
Sign up to set email alerts
|

Lay Public View of Neuroscience and Science-Based Brain Health Recommendations in Slovenia

Abstract: Background: Brain health is one of the cornerstones of a long and full life. Active care for brain health and reduction of lifestyle-related risks for brain disorders may be a key strategy in tackling the growing prevalence of mental and neurological illnesses. Public knowledge, perception, and preventive behavior need to be considered in the planning of effective strategies for brain health promotion. Our research is the first effort aimed at assessing Slovenian lay public knowledge, search and use of scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Studies conducted in France9 and the UK10 reported a lack of understanding of some mental disorders such as schizophrenia, bipolar disorders and autism. In Slovenia, a recent survey reported that, despite awareness of the importance of brain health, laypeople were unlikely to adopt purposefully behaviours beneficial for the brain due to lack of time and information 11. Qualitative studies conducted in the UK12 13 and elsewhere in Europe14 showed varying awareness of actions beneficial for the brain, and emphasised the importance of providing people with evidence-based and trustworthy information to encourage adoption of brain-friendly behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in France9 and the UK10 reported a lack of understanding of some mental disorders such as schizophrenia, bipolar disorders and autism. In Slovenia, a recent survey reported that, despite awareness of the importance of brain health, laypeople were unlikely to adopt purposefully behaviours beneficial for the brain due to lack of time and information 11. Qualitative studies conducted in the UK12 13 and elsewhere in Europe14 showed varying awareness of actions beneficial for the brain, and emphasised the importance of providing people with evidence-based and trustworthy information to encourage adoption of brain-friendly behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Confusion about which activities and factors benefit brain health has been apparent and illustrates the need for more evidence-based information regarding risk-reducing strategies. Although studies find people have positive intentions to change current brain health behavior, the intention-behavior gap is still high in the field of brain health as well ( 14 , 15 ). Symptoms of cognitive or mental decline, knowledge of disease risk or having family members with brain diseases are reported as some of the key motivating factors for behavioral changes ( 11 , 15 ).…”
Section: Introductionmentioning
confidence: 99%